Somatoform disorders. The first part: integrative model f pathology - A. A. Pribytkov; A. N. Erichev (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The problem of somatoform disorders (SFD) was regarded in accordance with the biopsychosocial concept of mental pathology. It was described the role of biological, social and psychological factors in the development of SFD. The representation of the interaction of these phenomena in the process of occurrence and further development of the SFD was gave. Predisposing factors (genetic predisposition, disturbance of neurotransmitters’ metabolism, misbalance of immune and endocrine systems, as well as personality’s typology), perpetuating factors (cognitive features, low opportunity of coping, abnormal behavior patterns, features of emotional response), precipitating factors (stress, social influence) were emphasized. Proposed multifactorial model can be used to improve care for patients who suffer from SFD, especially useful can be development of a cognitive-behavioral intervention.